Analisis Strategi Komunikasi Layanan Perpustakaan Universitas Riau Di Era Pandemi COVID-19 - Nurasmi; Deliza Zakir; Sumarni (Jurnal Gema Pustakawan, 2022)
The COVID-19 pandemic has changed the entire order of life, and has forced all libraries to innovate in order to continue to exist by implementing library communication strategies. This study aims to find out how the communication strategy of the Riau University library during the COVID-19 pandemic. The method used is a qualitative method with a descriptive approach. Data collection techniques were conducted by interview, observation, documentation, and literature study. Interviews were conducted with three internal library informants plus four external informants from among students. Data analysis was carried out with the stages of data reduction, data display, and finally data verification. The results showed that the communication strategy of the University of Riau library during the COVID-19 pandemic included three things, namely: 1) Running existing programs, 2) Developing applications for services in the form of e-forms, optimizing the use of social media in communication and information dissemination. . 3) Reducing sanctions. The conclusion of this study is that the service communication strategy carried out during the COVID-19 pandemic at the Riau University Library can have a positive impact on meeting the information needs of users.